Aplicações das funções exponenciais e logarítmicas - Rodrigues, Cristiano Santini (Universidade Federal de São Carlos, 2021)
This work aims to provide, within the Teaching of Mathematics, a greater interest, on the part of students, in the study of logarithms and their inverse, exponentials, based on the development of activities based on didactic hypotheses, involving problems and exercises within the scope of an understanding of the properties of these functions and analyzing the interdisciplinarity between disciplines, providing a meaningful and quality teaching.
Applications of exponential and logarithmic functions
Keywords: Ensino de matemática; Função logarítmica; Função exponencial; Interdisciplinaridade; Mathematics teaching; Logarithmic function; Exponential function; Interdisciplinarity; CIENCIAS EXATAS E DA TERRA::MATEMATICA::MATEMATICA APLICADA